ANALISIS PENINGKATAN MINAT BELI PADA RESTORAN SE’I SAPI LAMALERA MELALUI VARIABEL ELECTRONIC WORD OF MOUTH DAN CITRA MEREK PADA MAHASISWA INSTITUT TEKNOLOGI HARAPAN BANGSA - Rierie Andriani Larastanio; Laura Lahindah (Bina Ekonomi, 2020)
The rapid increase of the culinary business in the city of Bandung has caused culinary businessmen to have a competitive advantage to continue to survive in this business. Every part of this sector is used to allow it. This study aims to determine how many influences of e-WOM on brand image and performance on purchase intention. The object in this study was Se'i Sapi Lamalera. This study was conducted on 307 respondents using a quantitative descriptive approach. Therefore, data analysis is in the form of statistical analysis in the form of SEM-PLS. There is data processing using the Smart-Partial Least Square (Smart-PLS) version 3.0. PLS (Partial Least Square). The results of this study indicate that based on t test, e-WOM and brand image have a positive and significant effect on purchase intention in Se’i Sapi Lamalera and e-WOM has a positive and significant effect on purchase intention in Se'i Sapi Lamalera.